PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI HONORER DINAS BIMATARUNG PROVINSI SULAWESI TENGAH - NURHANISPA, NURHANISPA (Fakultas Ekonomi Universitas Tadulako, 2020)
The purrpose of this study was to determne and analyze the effect of compensation and work discipline simultaneusly and partialy on the performance of honorary employes of the Office of Highways and Spatial Planning of Prov. Central Sulawesi. The independent variabels of this studi are compensaton and work discipline. While the dependent variable is employee performance. The research method used is associative method with a sample of 62 people. form of sampling using census techniques. Data analysis method used in this study is a multiple linear regression analysis method. The results show that: 1). Compensation and work discipline simultaneously have a significant effect on the performance of honorary employees; 2). Partial compensation has a significant efect on the performance of honorary employees; 3). Work discipline partially has a significant efect on the performance of honorary employes of the Office of Highways and Prov. Central Sulawesi